Identificação de bergenina e carotenóides no fruto de uchi (Endopleura uchi, Humiriaceae) - Magalhães, Lyege Amazonas M. (Acta Amazonica, 2020)
The extract obtained in methanol from the fruits pulp of Endopleura uchi was fractionated using conventional chromatographic tecniques to isolate bergenin. In the analysis of the composition of carotenoids was evidenced the predominance of beta-carotene (16.57 mug.g-1). The isomers of beta-carotene: trans-beta-carotene (89.3%), 13-cis-beta-carotene (8%) and 9-cis-beta-carotene (3%) were detected. Considering the importance of the nutritional role of carotenoids and the bioactivity of the bergenina, this study suggested the potential of this fruit as functional food.